Experimental Study on Vertical Propagation Behavior of Hydraulic Fracture Affected by Artificial Interlayer for Thick Oil Reservoirs - Beibei Chen; Yingmin Qin; Peng Xu; Weijie Zheng; Min Zhang; Yan Peng (Geofluids)
Crude oil distribution in thick oil reservoirs is vertically heterogeneous; therefore, there is usually a dominant sublayer where oil resources are higher than that in other sublayers. The region of hydraulic fracture away from the dominant sublayer plays a negative role in production. In order to enhance efficiency of hydraulic fracturing, the hydraulic fracture height should be restricted around the dominant sublayer and the artificial interlayer is believed as an effective method. However, the propagation mechanism of fracture affected by artificial interlayer has been rarely investigated, which restricts the advance of optimization of artificial interlayer. In this paper, the impact of artificial interlayer on vertical propagation of hydraulic fracture is analyzed by hydraulic fracturing experiments and then the mechanism of artificial interlayer affecting propagation of hydraulic fracture is discussed. Based on the understanding of experimental observations and theory of fracture mechanics, the theoretical model of stress intensity factor for the fracture affected by artificial interlayer is proposed. The experimental data shows that the artificial interlayer can significantly decrease the hydraulic fracture height and the corresponding decrease magnitude of hydraulic fracture height depends on the thickness of artificial interlayer, proppant size, and fracture fluid pumping rate. The dominant mechanism of artificial interlayer restricting hydraulic fracture height is that the drop of fluid pressure induced by the artificial interlayer decreases the stress intensity factor at fracture tip. Based on the theory of fracture mechanics, the stress intensity factor at fracture tip is built and it can consider key factors shown by experimental observations. The fracture height solution from this model is consistent with experimental data, so this model can be used to optimize properties of artificial interlayer.